bis-Pyridinium Cyclophanes: Novel Ligands with High Affinity for the Blood-Brain Barrier Choline Transporter - Zhang, Zhenfa (2008)
A series of bis-pyridinium cyclophane analogs designed as conformationally-restricted bis-quaternary ammonium compounds were evaluated for their affinity for the blood-brain barrier (BBB) choline transporter. All the cyclophanes investigated exhibited high affinity compared to choline. Of these compounds, N, N’-(1, 10-decanediyl)3, 3’-(1, 9-decadiyn-1, 10-diyl)-bis-pyridinium diiodide (5c) and N, N’-(1, 9-nonanediyl)3, 3’-(1, 9-decadiyn-1, 10-diyl)-bis-pyridinium dibromide (5b) exhibited highest affinity with K(i) values of 0.8 µM and 1.4 µM, respectively, and constitute some of the most potent BBB choline transporter ligands reported.